PENGARUH KEUNGGULAN PRODUK, REPUTASI PERUSAHAAN DAN ASOSIASI MEREK TERHADAP KESUKSESAN PRODUK BARU DALAM MENINGKATKAN KINERJA PEMASARAN (Studi Pada CounterSmartphone BlackBerry di Kota Semarang) (Jurnal Mahasiswa Pasca Sarjana, 2015)
Level successfulness of new product for example influenced by excellence of product, company reputation and brand association. Excellence of product represent one of the determinant of successfulness of new product beside influence of company reputation and brand association. Indicator a[n successful product or market do not is product become leader of market, becoming purchasing priority and lower complain. Successfulness of new product influence marketing performance. In this research is obtained by four hypothesis which have been tested. collected data from 135 responder coming from or owner of supervisor outlet seller of product of Smatphone BlackBerry in The Semarang City. Analyzer the used is to use program of statistic SPSS relase windows for 16. Result of data analysis show research result and model earn some of can be accepted. Result of this research prove that variable excellence of product have an effect on and [do] not signifikan to kesuksusesan of new product, while company reputation and brand association have an effect on to successfulness of new product. Whereas variable successfulness of new product have an effect on and do not signifiqion to marketing performance. Keyword: Excellence of Product, company reputation, brand association, successfulness of new product, marketing performance.